Is Being a Good Empiricist the Same as Being a Good Naturalist? The Case of the Relationship Between Science and Christian Theism - Bylica, Piotr (Filozoficzne Aspekty Genezy, 2023)
Using Feyerabend’s argumentation, and rephrasing of the problem in terms of the Model of Levels of Analysis, I show that a good empiricist need not be a (metaphysical or methodological) naturalist. I characterize the ideas of Alvin Plantinga and Jitse M. van der Meer as being representative of two different varieties of theistic response to the problem of the relationship between Christianity and contemporary science. Against van der Meer, I argue for Plantinga’s conclusion about the value of theism-based science. Against both approaches, I point to situations where theistic assumptions do indeed influence the contents of observation.